Asesmen Katalog Gempabumi di Wilayah PGR III Sebelum dan Setelah Penambahan Sensor Seismik Tahun 2019 Menggunakan Magnitude Completeness - I Putu Dedy Pratama; Mario Charlos Rohi Koten; Pande Komang Gede Arta Negara (Buletin GAW Bariri, 2021)
To improve the quality of earthquake information, 8 seismic sensors were added in the PGR III region in 2019 and began to be used in earthquake analysis by 4 geophysical stations in early 2020. The results of the analysis are in the form of an earthquake catalog that needs to be evaluated to see the impact of adding sensors to the magnitude completeness from the catalog. The data used from the Sistem Penentu Keputusan (SPK) earthquakes catalog in the PGR III region with data before the addition of new sensors using 2019 data and after addition using 2020 data. To determine the changes in the completeness of the earthquake catalog, the Magnitude Completeness (Mc) was calculated using four methods (Maximum Curvature (MAXC), Goodness–of–Fit Test (GFT), Mc by b – value Stability (MBS), Entire Magnitude Range (EMR), dan Entire Magnitude Range (EMR)) in the catalog before and after adding 8 declustered seismic sensorsIn addition, spatial and temporal analysis was conducted to determine the time and space that experienced changes in Mc. There was a decrease in the value of Mc in the MAXC and MBS methods in the catalog after the addition of new sensors, while the GFT and EMR methods had the same values ​​for both the 2019 and 2020 catalogs. Before adding new sensors Mc values range between ​​1.4–2.8 and after adding new sensors the Mc value ranges between 0.9–2.8. Spatially, the value of Mc, measured by the seismic activity in the area as well as the density of the sensor distribution where the denser the sensor distribution and increasing the seismic activity can reduce the value of the Mc. With the addition of seismic sensors that can improve the completeness of the earthquake catalog in the PGR III region in earthquake analysis. This can be seen from the decrease in the value of Mc in the area with the addition of new sensors and the decrease in the gradient of the Mc value with time.